Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi Dalam Melaporkan Spt Tahunan Pada Masa Pandemi Covid-19 Di Kpp Pratama Bukittinggi - Crisvanya Monica; Notika Rahmi (Jurnal Pajak Vokasi (JUPASI), 2022)
This study aims to examine the factors that influence individual taxpayer compliance in reporting tax returns at the Bukittinggi Pratama Tax Service Office using several independent variables that have also been used in previous research such as knowledge of taxation, tax service services and mandatory awareness. tax. This study uses a quantitative approach. The population in this study is individual taxpayers (WPOP) at KPP Pratama Bukittinggi. Sampling was done by convenience sampling method. The number of samples is determined by 105 people. The primary data collection method used is the questionnaire method (questionnaire). The data analysis technique used in this research is multiple regression analysis technique. Based on the results of the analysis, it can be concluded that knowledge of taxation has a significant positive effect of 44.8% and taxpayer awareness has a significant positive effect of 44% on taxpayer compliance, while the tax service service does not have a significant effect of 37%. Knowledge of taxation, tax service services, and taxpayer awareness together have a positive 54.7% effect on taxpayer compliance.